Flexibilité vocale sous influences sociales chez les primates non-humains - Hélène Bouchet; Marion Laporte; Agnès Candiotti; Alban Lemasson (Revue de Primatologie)
Animal vocal communication, as human language, is primarily a social act. It is therefore legitimate to argue in favor of a coevolution between sociality and vocal complexity in primates. However, in contrast with human language, vocal communication in monkeys and apes, our closest living relatives, has long been described as rigid and strongly genetically determined. In recent years, evidences of vocal flexibility under social influences have nonetheless been provided in nonhuman primates. In this paper, we review those recent findings that challenge the dichotomous view of human versus monkey regarding vocal communication. First, a multi-level approach (sound unit, call type, vocal sequence) of the structure of vocal repertoire reveals a flexible organization which enables a complex encoding of messages in vocal signals. Then, the analysis of the social context of communicative interaction demonstrates its role in the emergence of vocal flexibility in juveniles and adults, both in terms of production and usage. We conclude by emphasizing the need, in the future, for additional comparative studies in order to assess the influence of the characteristics of social system on the degree of communicative flexibility and complexity observed at the species level.